前言：科技興趣、超越人類與倫理限制: Introduction: Technological Interests, Transhumanism and Ethical Commitments - CAI, Yu; FAN, Ruiping (International Journal of Chinese & Comparative Philosophy of Medicine, 2021)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 人類正處於前所未有的技術高速發展時代。特別是，NBIC技術（納米技術、生物技術、資訊技術和認知科學）彙集起來的發展，使得人類改造自身、進而超越自身的夢想不斷接近現實，但也為我們敲響了倫理學的警鐘：如果我們對生命技術的不斷突破和廣泛應用所牽涉的倫理價值缺乏充分的考量並施以必要的限制，那麼技術就無法得到有利的發展和公平的應用，甚至造成過分追求那些具有不可逆結果或不可逆傷害的生命技術的後果，使得現代生物醫學成為人類幸福的一種“錯誤承諾”。本期的兩篇主題論文以及十六篇評論文章，正是著力於探討這些影響深遠的生命倫理問題。 This issue of the journal contains two thematic papers, namely “Emerging Human Embryo Research Technologies, the 14-day Rule, and the Special Status of the Embryo” by Kirstin R. W. Matthews, Sam Lowe, and Ana S. Iltis, and “A Confucian Reflection on Transhumanism: How to Regulate Our Posthuman Future?” by Wang Jue, in addition to 16 commentary essays on ethical issues associated with rapidly developing biomedical technologies. The authors argue that scientific interests should not be the main driver of technological breakthroughs and applications. Rather, ethical commitments embedded in cultural traditions should play a positive role through public participation in legitimate policymaking.